FORMULATION AND EVALUATION OF FEBUXOSTAT FAST DISSOLVING TABLETS USING ENTADA SCANDENS SEED STARCH AND POLOXAMER-188 AS SUPERDISINTEGRANTS - DOPPALAPUDI, SANDEEP; SURYADEVARA, VIDYADHARA; JUJALA, CHIRUDEEP (International Journal of Applied Pharmaceutics, 2019)
Objective: The present study focused on solubility enhancement of the Biopharmaceutical Classification System (BCS) Class-II drug, Febuxostat using various super disintegrants. Methods: Starches were extracted from Entada scandens seed powder by alkali method i.e., sodium hydroxide at 0.1%, 0.25% and 0.5% concentrations and water. Starches were evaluated for various phytochemical and physicochemical tests. Solid dispersions of Febuxostat were prepared by fusion method using poloxamer-188 alone and by mixing poloxamer-188 with Entada scandens seed starch. Various physical parameters were evaluated for these solid dispersions. Tablets were prepared using Febuxostat solid dispersions and varying concentrations of Entada scandens seed starch by direct compression technique. Pre and post-compression parameters were evaluated along with in vitro drug release studies, characterization studies like Fourier Transform Infra-Red spectroscopy (FTIR), Differential Scanning Calorimetry (DSC), Scanning Electron Microscopy (SEM), X-Ray Diffraction (XRD) and stability studies. Results: Phytochemical tests revealed the presence of starch in all extracts. Starch prepared from 0.5% sodium hydroxide (ESS4) showed best physicochemical properties. In vitro dissolution studies revealed that solid dispersion F4 containing Febuxostat and poloxamer-188 in 1:3 ratios showed better drug release. Formulation FE5 containing F4 solid dispersion with 12.5% w/w of ESS4 showed enhanced drug release. FT2 tablets having 12.5% w/w of ESS4 showed better drug release when compared to others. FTIR and DSC studies revealed no major interactions between drug and excipients. XRD studies revealed the nature of formulations. Accelerated stability studies showed that all tablets were stable. Conclusion: The super disintegrant property of Entada scandens seed starch was evaluated.